Endurance training volume cannot entirely substitute for the lack of intensity - Matomäki, Pekka; Heinonen, Olli J.; Nummela, Ari; Kyröläinen, Heikki (Public Library of Science (PLoS), 2025)
Purpose: Very low intensity endurance training (LIT) does not seem to improve maximal oxygen uptake. The purpose of the present study was to investigate if very high volume of LIT could compensate the lack of intensity and is LIT affecting differently low and high intensity performances.
Methods: Recreationally active untrained participants (n = 35; 21 females) cycled either LIT (mean training time 6.7 ± 0.7 h / week at 63% of maximal heart rate, n = 16) or high intensity training (HIT) (1.6 ± 0.2 h /week, n = 19) for 10 weeks. Two categories of variables were measured: Low (first lactate threshold, fat oxidation at low intensity exercise, post-exercise recovery) and high (aerobic capacity, second lactate threshold, sprinting power, maximal stroke volume) intensity performance.
Results: Only LIT enhanced pooled low intensity performance (LIT: p = 0.01, ES = 0.49, HIT: p = 0.20, ES = 0.20) and HIT pooled high intensity performance (LIT: p = 0.34, ES = 0.05, HIT: p = 0.007, ES = 0.48).
Conclusions: Overall, very low endurance training intensity cannot fully be compensated by high training volume in adaptations to high intensity performance, but it nevertheless improved low intensity performance. Therefore, the intensity threshold for improving low intensity performance is lower than that for improving high intensity performance. Consequently, evaluating the effectiveness of LIT on endurance performance cannot be solely determined by high intensity performance tests.